1995
DOI: 10.1002/elan.1140071006
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene‐containing polymers as electron transfer mediators in carbon paste electrodes modified with PQQ‐dependent aldose dehydrogenase

Abstract: The aim of this work was to improve an aldose-detecting biosensor based on quinoprotein aldose dehydrogenase (ALDH). Polymer-bound ferrocene derivatives with four different structures were studied as electron transfer mediators between the coenzyme of ALDH, pyrroloquinoline qninone (PQQ), and the conducting electrode material. The ferrocene polymers were mixed into carbon paste, which was used for the preparation of aldose-detecting electrodes by immobilizing ALDH on the carbon paste surface by adsorption. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…There are a number of other sugar oxidizing enzymes with bound cofactors. Some of them have been previously used for biosensor constructions, e.g., hexose oxidase [7], oligosaccharide dehydrogenase [8 -10], aldose dehydrogenase [11], cellobiose dehydrogenase [12,13], carbohydrate oxidase [14] and pyranose oxidase [15,16]. In the present work, electrical wiring of various forms of two different sugar oxidizing enzymes, i.e., pyranose oxidase (P2O), both wild type and a mutant, as well as one commercial P2O, and additionally pyranose dehydrogenase (PDH) from two different origins, with an osmium redox polymer, (poly(1-vinylimidazole) 12 -[Os(4,4'-dimethyl-2,2'-dipyridyl) 2 Cl 2 ] 2þ/þ ), is reported.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of other sugar oxidizing enzymes with bound cofactors. Some of them have been previously used for biosensor constructions, e.g., hexose oxidase [7], oligosaccharide dehydrogenase [8 -10], aldose dehydrogenase [11], cellobiose dehydrogenase [12,13], carbohydrate oxidase [14] and pyranose oxidase [15,16]. In the present work, electrical wiring of various forms of two different sugar oxidizing enzymes, i.e., pyranose oxidase (P2O), both wild type and a mutant, as well as one commercial P2O, and additionally pyranose dehydrogenase (PDH) from two different origins, with an osmium redox polymer, (poly(1-vinylimidazole) 12 -[Os(4,4'-dimethyl-2,2'-dipyridyl) 2 Cl 2 ] 2þ/þ ), is reported.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Smolander et al reported a PQQ-aldose dehydrogenase modified carbon paste (CP) electrode for flow-injection analysis of aldose sugars. 25,26 They succeeded to improve the sensor stability by preventing leaking of the enzyme with a polymer external membrane. However, long-term stability was certified only for one day, and it was insufficient for practical use.…”
Section: Introductionmentioning
confidence: 99%
“…In addition the presence of oxygen does not affect the catalytic activity of the enzyme, which is a problem in the case of glucose oxidase. ALDH enzyme was previously shown to work in amperometric sensors for xylose and glucose [3,4,11]. Due to the two electron oxidation reaction of glucose:…”
Section: Introductionmentioning
confidence: 99%